2022
DOI: 10.1371/journal.pone.0262113
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative fever after liver resection: Incidence, risk factors, and characteristics associated with febrile infectious complication

Abstract: Purpose To evaluate the incidence and risk factors of postoperative fever (POF) after liver resection. In patients with POF, predictors of febrile infectious complications were determined. Methods A total of 797 consecutive patients undergoing liver resection from January 2015 to December 2019 were retrospectively investigated. POF was defined as body temperature ≥ 38.0°C in the postoperative period. POF was characterized by time of first fever, the highest temperature, and frequency of fever. The Institut M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
1
0
1
Order By: Relevance
“…Sustaining higher levels of albumin contributes to the protection of the body, helping to mitigate physiological stress responses induced by inflammation [5]. Consequently, timely albumin supplementation postoperatively can effectively reduce the likelihood of postoperative fever in patients undergoing total hip arthroplasty (THA).Research by Lai HF et al [6] suggested that postoperative serum albumin levels below 32g/L are one of the contributing factors to postoperative fever. In our study, patients with low postoperative albumin levels exhibited a significantly higher incidence of fever compared to the non-fever group.…”
Section: Discussionmentioning
confidence: 99%
“…Sustaining higher levels of albumin contributes to the protection of the body, helping to mitigate physiological stress responses induced by inflammation [5]. Consequently, timely albumin supplementation postoperatively can effectively reduce the likelihood of postoperative fever in patients undergoing total hip arthroplasty (THA).Research by Lai HF et al [6] suggested that postoperative serum albumin levels below 32g/L are one of the contributing factors to postoperative fever. In our study, patients with low postoperative albumin levels exhibited a significantly higher incidence of fever compared to the non-fever group.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative infection is a frequent complication of hepatic resection, with reported rates of up to 25%[ 77 , 78 ]. It can be associated with significant morbidity in the absence of early recognition and treatment[ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2014) продемонстрировали, что обширная гепатэктомия была связана с более высокой частотой инфекционных осложнений (инфекции органов/полостей, поверхностных кожных инфекций, пневмонии, сепсиса и септического шока) [23]. После массивных резекций печени у половины пациентов может наблюдаться развитие послеоперационной лихорадки, которая в 12% случаев заканчивается развитием сепсиса [24]. По данным другого исследования, частота послеоперационной инфекции может достигать 50% после большой резекции печени, а бактериальная инфекция может развиться у 80% пациентов с ПрПН по сравнению с 20% пациентов без ПрПН [25].…”
Section: цельunclassified